Improvement and Quantification of Spatial Accessibility and Disturbance Responsiveness of Shoulder Prosthesis. (13th February 2015) - Sekine, Masashi; Xie, Le; Kawamura, Kazuya; Yu, Wenwei
Transhumeral and shoulder disarticulation amputees find it difficult to move their prostheses for goal-oriented movement using only their small residual limbs. Thus, spatial accessibility is especially important for shoulder prostheses. Moreover, because responding to external disturbances and absorbing impact using only the viscoelasticity and flexibility of the small residual limb is difficult, the intrinsic viscoelasticity of the shoulder prosthesis is indispensable for safety. In our previous work, we proposed a small pneumatic elastic actuator-driven parallel link mechanism for shoulder prostheses. In this paper, we propose two new devices, a sliding antagonistic mechanism and a soft backbone, to improve the spatial characteristics and disturbance responsiveness. We quantitatively evaluated a prosthetic arm with the two devices. The results showed that the two devices increased the arm's workspace and disturbance responsiveness.